2022
DOI: 10.3390/foods11111577
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Development of Nontoxic Nonproteolytic Clostridium botulinum Surrogate Strains for Food Challenge Testing

Abstract: Clostridium botulinum causes severe foodborne intoxications by producing a potent neurotoxin. Challenge studies with this pathogen are an important tool to ensure the safety of new processing techniques and newly designed or modified foods, but they are hazardous and complicated by the lack of an effective selective counting medium. Therefore, this study aimed to develop selectable nontoxic surrogate strains for group II, or nonproteolytic, C. botulinum, which are psychotropic and hence of particular concern i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…With these data in mind, it has previously been proposed to consider not only physiologic differences but also the genomic distribution of strains for food safety studies [ 36 , 67 ]. Genomic SNP phylogenetic analysis of the 10-strain cocktail used in this study showed that the strains were predominantly distributed into the same lineages that Brunt et al determined to have higher numbers of food isolates ( Figure 1 ) [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With these data in mind, it has previously been proposed to consider not only physiologic differences but also the genomic distribution of strains for food safety studies [ 36 , 67 ]. Genomic SNP phylogenetic analysis of the 10-strain cocktail used in this study showed that the strains were predominantly distributed into the same lineages that Brunt et al determined to have higher numbers of food isolates ( Figure 1 ) [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the diversity of strains selected for food challenge cocktails is an important consideration, previous studies have suggested that it is also important to ensure that inhibition between strains is minimized, as the antagonistic activity may alter toxin production [ 67 , 68 ]. Two strains within the strain cocktail studied here have previously been reported to contain genes that encode inhibitory compounds, the boticin B from strain 213B [ 38 ] and the endolysin LysB from strain Alaska E [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the threat posed by the pathogenicity of C. botulinum , it is recommended to perform challenge tests using surrogates with properties identical to those exhibited by the pathogen except for the ability to produce botulinum toxins. The use of surrogate organisms makes it possible to determine the optimal conditions for preventing the growth of C. botulinum , thus providing a more reliable way of manufacturing products free of microbiological hazards ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, growth tests or food challenges with surrogate microorganisms may be considered. Such surrogate strains of C. botulinum group I and group II have been proposed ( Boix et al, 2022 ; Koukou et al, 2022 ; Poortmans et al, 2022 ). Data and models established with C. sporogenes as a surrogate of C. botulinum group I can help to define the control measures to prevent growth ( Boix et al, 2022 ; Koukou et al, 2022 ).…”
Section: Botulism and Animalsmentioning
confidence: 99%